A STUDY REGARDING THE ASSESSMENT OF THE PHYSICAL TRAINING LEVEL DURING STRENGTH TO POWER CONVERSION PHASE AT JUNIOR SPRINTER LEVEL FOR PRE-COMPETITION STAGES (GYMNASIUM, 2009)
overcomes the hurdles set by certain training patterns.Progress during the junior period is very important and therefore we consider that strength to powerconversion during pre-competition and competition stages can provide adequate strength training in order toachieve remarkable performance.The importance of strength to power conversion was demonstrated by the higher level obtained bythe specific and non-specific control events indicators, gradually increasing after successive tests, as well asby the improved results in competition events.The use of strength to power conversion exercises will be administered individually depending onthe athlete’s training level, the period or stage of training as well as on the training conditions.